Perceived fairness as main determinant of patients' satisfaction with care during psychiatric hospitalisation: An observational study. (May 2022) - Silva, Benedetta; Pauli, Guillaume; Diringer, Oana; Morandi, Stéphane; Bonsack, Charles; Golay, Philippe
Abstract: Introduction: Patient satisfaction with care is widely recognized as one of the most important indicator of quality in mental health care. It can impact several treatment outcomes, such as treatment adherence and engagement with services. At the same time, as an outcome in itself, satisfaction with care is also affected by several factors, first and foremost by being coerced. The main aim of this study was to test if perceiving treatment pressures as fair and effective could positively impact patient satisfaction, even more than formal coercive measures. Methods: Globally, 133 voluntary and involuntary inpatients were interviewed. Socio-demographic and clinical characteristics, including history of previous experiences of formal coercion and legal status of the hospitalisation, were collected through a structured questionnaire and medical charts. The participants were also asked to complete the Index of Fairness and Index of Effectiveness tools as well as a structured questionnaire on satisfaction with care. Simple and multiple linear regressions were performed. Results: Although several factors were found to affect satisfaction with care when taken independently, perceived fairness was the stronger predictor of both satisfaction with treatment (β =.234; p = .022) and satisfaction with decision-making involvement (β =.360; p < .001) when controlling for confounders. Conclusions: Our results point to the paramount importance of developing and implementing interventions that promote procedural fairness in psychiatric treatment and thereby improve patient satisfaction while reducing the risk of disengagement with care.